The relationship between muscle strength, anaerobic performance, agility, sprint ability and vertical jump performance in professional basketball players - Alemdaroglu, U. (Journal of Human Kinetics, 2012)
The purpose of this study was to investigate the relationship between isokinetic knee strength, anaerobic performance, sprinting ability, agility and vertical jump performance in first division basketball players. Twelve male first division basketball players participated in this study. The mean age was 25.1 +/- 1.7 yrs; mean body height 194.8 +/- 5.7 cm; mean body mass 92.3 +/- 9.8 kg; mean PBF 10.1 +/- 5.1; and mean VO2max 50.55 +/- 6.7 ml/kg/min. Knee extension and flexion strengths were measured at 60o and 180./s, anaerobic performance was evaluated using the Wingate anaerobic power test, sprint ability was determined by single sprint performance (10-30 m), jump performance was evaluated by countermovement (CMJ) and squat jump (SJ) tests and agility performance was measured using the T drill agility test. Extension strength was significantly correlated with peak power at all contraction velocities. However, for mean power, significant correlation was only found between the 60o left and 180o right knee extension strength measurements. No measure of strength was significantly related to the measurements from/results of field tests. Moreover, strong relations were found between the performance of athletes in different field tests (p< 0.05). A limitation of the current study is the use of correlation analysis. Correlations do not prove causation, rather that two variables are related in some way. Within these limitations, the current results highlight the need for a comprehensive battery of field tests to evaluate performance in basketball players.